2002
DOI: 10.1046/j.1529-8817.2002.00170.x
|View full text |Cite
|
Sign up to set email alerts
|

LONG‐TERM CHANGES IN THE MACROALGAL VEGETATION OF THE INNER GULLMAR FJORD, SWEDISH SKAGERRAK COAST1

Abstract: We examined long‐term changes in the macroalgal vegetation at Stora Bornö Island in the inner Gullmar Fjord on the Swedish Skagerrak coast. This was made possible by access to a 1941 diving investigation. The same sites were reinvestigated in 1998. Community composition and depth distributions of species were compared and changes were analyzed with focus on functional groups (size, thallus shape, and life‐history traits). We discovered a significant decrease in the depth extension of macroalgal species and a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 42 publications
2
90
0
Order By: Relevance
“…The effects of pollution on macroalgal assemblages have been reported in previous studies (Bellan-Santini 1968, Munda 1974, Anger 1975, Littler and Murray 1975, Murray and Littler 1978, Belsher 1979, Kautsky et al 1986, Hardy et al 1993, Soltan et al 2001, and several works have examined long-term changes following the onset of sewage discharge , Gorostiaga and Díez 1996, Underwood and Chapman 1996, Díez et al 1999, Bishop et al 2002, Eriksson et al 2002, Echevarri-Erasun et al 2007. However, only a few studies have focused on the recovery of macroalgal assemblages following clean-up measures (Hardy et al 1993, Bokn et al 1996, Archambault et al 2001, Díez et al 2009), and only two have addressed Mediterranean communities (Soltan et al 2001, Tsiamis et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of pollution on macroalgal assemblages have been reported in previous studies (Bellan-Santini 1968, Munda 1974, Anger 1975, Littler and Murray 1975, Murray and Littler 1978, Belsher 1979, Kautsky et al 1986, Hardy et al 1993, Soltan et al 2001, and several works have examined long-term changes following the onset of sewage discharge , Gorostiaga and Díez 1996, Underwood and Chapman 1996, Díez et al 1999, Bishop et al 2002, Eriksson et al 2002, Echevarri-Erasun et al 2007. However, only a few studies have focused on the recovery of macroalgal assemblages following clean-up measures (Hardy et al 1993, Bokn et al 1996, Archambault et al 2001, Díez et al 2009), and only two have addressed Mediterranean communities (Soltan et al 2001, Tsiamis et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…These authors also point out that there are questions such as nutrient uptake efficiency where these models would be useful. In this way, Eriksson et al (2002) suggest that small, thin, filamentous species were favoured at the expense of large, complex algae on the Swedish Skagerrak coast as result of an eutrophication process. There is also considerable documentation (Munda, 1993;Rodrı´guez-Prieto & Polo, 1996;Are´valo et al, 2007;Pinedo et al, 2007) and experimental support (Benedetti-Cecchi et al, 2001;Gorgula & Connell, 2004) for the loss of large canopy-forming algae in favour of turf-forming algae as a consequence of anthropogenic disturbances.…”
Section: Functional/morphological Groupsmentioning
confidence: 99%
“…Shallow enclosed or semi-enclosed water bodies exhibit worldwide an increased algal growth due to eutrophication (Schramm & Nienhuis, 1996); in these environments, pollution abatement could give rise to a reduction in algal cover (Schernewski & Neumann, 2002). However, eutrophication results in a generally lower light regime and in increased organic sedimentation, factors that seem to entail algal cover decline below the first few metres in depth (Eriksson et al, 2002). Similarly, Krause-Jensen et al (2007) found that total macroalgal cover responds to differences in water quality and salinity between Danish coastal areas, increasing in clear waters and with salinity.…”
Section: Algal Covermentioning
confidence: 99%
See 2 more Smart Citations